Future Computing, Communication, Control and Management Volume 2 - Zhang, Ying.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume contains revised and extended research articles written by prominent researchers participating in the ICF4C 2011 conference. 2011 International Conference on Future Communication, Computing, Control and Management (ICF4C 2011) has been held on December 16-17, 2011, Phuket, Thailand. Topics covered include intelligent computing, network management, wireless networks, telecommunication, power engineering, control engineering, Signal and Image Processing, Machine Learning, Control Systems and Applications, The book will offer the states of arts of tremendous advances in Computing, Communication, Control, and Management and also serve as an excellent reference work for researchers and graduate students working on Computing, Communication, Control, and Management Research.
From the content: Towards the Web of Things: Open Research Issues and the BAS-AMI Use Case -- A Positioning Research of Underwater Acoustic Sensor Networks Based on Support Vector Regression -- The Design of Vehicle Traveling Data Recorder Based on GPS/GPRS -- A solution for the locus management of information cards -- Vector-based distributed mobile communication core-network intrusion alarm system -- Technology Analysis to the Security and Reliability in Network Transactions -- A Novel AISA-based Resource Scheduling Method for Reader Collision Problem in RFID Systems.
Keywords: Engineering; Information systems; Computer engineering; Telecommunication; Industrial management; Engineering; Communications Engineering, Networks; Control; Electrical Engineering; Management/Business for Professionals; Information Systems and Communication Service